Sustainability index: application for the municipalities of Ilha do Maranhão. - Morais , Cintia Maria de Aguiar; Reis Neto, José Francisco dos (National Journal of City Management, 2023)
The article aims to estimate the sustainability index (SI) for the municipalities of Ilha do Maranhão and verify if they adapt to the concepts of sustainable cities discussed in the context of emerging international conferences since the 1980s and more specifically regarding the 2030 Agenda through SDG 11- Sustainable cities and communities. The methodology used was based on applied research for the construction of the IS with the use of quantitative research based on the ABNT indicator system NBR ISO 37120:2017. As an outcome, it was noticed that those indicators are applicable to the municipalities, even with the limitations due to the partial collection of data as well as the obsolete basis for public research. Considering the results obtained for the municipalities, it was identified that they range from acceptable to regular regarding the condition of sustainability and compliance with SDG 11.